A COMPARATIVE ANALYSIS FOR THE ADMINISTRATION OF UNDISTRIBUTED FUNDS IN THE ESTATES DISTRIBUTION FOR PERSON LACKS LEGAL CAPACITY - Rahmawati Mohd Yusoff; Rosnani Mohd Salleh; Norintan Wahab (Journal of Islamic, Social, Economics and Development, 2023)
A person of unsound mind means a person which is found incapable of managing himself and his affairs. Upon the conclusion of estates distribution, the law provides that undistributed funds for person lacks legal capacity, for example in cases of minor, insane or senile may be passed to the Public Trust Corporation that will act as a trustee for such funds. The purpose of this paper is to examine the governing law relating to the administration of the undistributed funds in the estates distribution and the issues relating to it. The analysis is based on a qualitative and descriptive cross-sectional analysis of the governing statutes, reported cases, and data gathered from the respective administrative authorities. For the comparative analysis, the research also provides the reference of the system for the administration of undistributed funds in Singapore and the United Kingdom. The research found that the administration of undistributed funds in Malaysia is governed by the Probate and Administration Act 1959 (Act 97), Public Trust Corporation Act 1995 (Act 532), and Small Estates (Distribution) Act 1955 (Act 98). It can be inferred that, as the provision only uses the word (may) instead of (shall) there is no mandatory requirement for the personal representative to deposit the undistributed funds with the Public Trust Corporation. It is mainly due to the fact that the personal representative also assumed the duties of trustee as provided under the Trustee Act 1949.